Keefektifan Discovery Bible Study Group: Sebuah Metode Sederhana Dalam Pemuridan - Yesika Samosir; Riston Batuara (Predica Verbum: Jurnal Teologi dan Misi, 2023)
This study aims to explore the effectiveness of Discovery Bible Study (DBS) in groups commonly referred to as Discovery Groups as a method of bringing life transformation and spiritual growth and moving participants to live in obedience. The research approach used was a literature study by analyzing various literatures and other relevant data sources. The findings of this study show that the Discovery Bible Study is able to support and contribute to the effectiveness of forming Fellowship and Prayer, creating Accountability (Responsibility), increasing people's Understanding of God's Word through the process of self-discovery, and motivating people or participants to live in Obedience in transforming, sharing, and discipling others.